Costs of production and labour productivity: 1978 and 1983 Malaysian vintage technology - Ab. Rashid, Zakariah (Penerbit Universiti Kebangsaan Malaysia, 1991)
By using the 1978 and 1983 Malaysian input-output tables, the paper attempts to determine differences in costs of production caused by changing price structure. Appropriate price indices for producer and import prices and wage rates are formulated involving cost-transformation of product and trade classifications when input-output classification is adopted. The paper estimates sectoral costs of production (including labour) for each vintage and their levels measure technological change and obsolescence. It also estimates total labour requirements for each vintage. It was found that older (younger) vintage has higher (lower) costs of production and requires more (less) labour.